Commodity risk assessment of Petunia spp. and Calibrachoa spp. unrooted cuttings from Guatemala - EFSA Panel on Plant Health (PLH); Claude Bragard; Paula Baptista; Elisavet Chatzivassiliou; Francesco Di Serio; Paolo Gonthier; Josep Anton Jaques Miret; Annemarie Fejer Justesen; Alan MacLeod; Christer Sven Magnusson; Panagiotis Milonas; Juan A. Navas‐Cortes; et al. (EFSA Journal)
Abstract The European Commission requested the EFSA Panel on Plant Health to evaluate the probability of entry of pests (likelihood of pest freedom at entry), including both, regulated and non‐regulated pests, associated with unrooted cuttings of the genera Petunia and Calibrachoa produced under physical isolation in Guatemala. The relevance of any pest for this opinion was based on evidence following defined criteria, based on the methodology used for high‐risk plants adapted for the specificity of this assessment. Twenty EU regulated pests (Bemisia tabaci, pepper golden mosaic virus, pepper huasteco yellow vein virus, squash leaf curl virus, tomato severe leaf curl virus, tomato yellow leaf curl virus, tomato spotted wilt virus, Liriomyza huidobrensis, Liriomyza sativae, Liriomyza trifolii, Bactericera cockerelli, Eotetranychus lewisi, Epitrix subcrinita, Epitrix cucumeris, Helicoverpa zea, Chloridea virescens, Spodoptera ornithogalli, Ralstonia solanacearum, Ralstonia pseudosolanacearum, Xanthomonas vesicatoria) and one EU non‐regulated (Phenacoccus solenopsis) pest fulfilled all relevant criteria and were selected for further evaluation. For these pests, the risk mitigation measures proposed in the technical dossier from Guatemala were evaluated taking into account the possible limiting factors, and an expert judgement is given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The limited and partially conflicting information provided in the dossier contributes to the wide estimates of pest freedom. The estimated degree of pest freedom varies among the pests evaluated, with Ralstonia spp. (R. solanacearum and R. pseudosolanacearum) being the pest most frequently expected on the imported cuttings. The expert knowledge elicitation indicated, with 95% certainty, that between 9916 and 10,000 bags containing unrooted cuttings per 10,000 would be free of Ralstonia spp.